2012
DOI: 10.1086/664826
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Regulation of Redox State and Some Biotransformation Enzyme Activities in the Barn Swallow (Hirundo rusticaL.)

Abstract: Little is known of the normal seasonal variation in redox state and biotransformation activities in birds. In long-distance migratory birds, in particular, seasonal changes could be expected to occur because of the demands of migration and reproduction. In this study, we measured several redox parameters in the barn swallow (Hirundo rustica L.) during the annual cycle. We captured the wintering barn swallows before spring migration in South Africa, and we captured the barn swallows that arrived in spring, bred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
2
15
2
1
Order By: Relevance
“…Hence, moult may result in redox imbalance, but this topic has not been thoroughly addressed. A previous study showed that barn swallows (Hirundo rustica) at initial stages of flight feather moult had higher glutathione S-transferase activity and lipid hydroperoxides than birds that had nearly terminated moult, suggesting that moult, either directly or indirectly via increased energy expenditure due to handicapped flight, may cause oxidative stress (Raja-aho et al, 2012). Our findings strongly suggest that moult resulted in higher protein oxidative damage (reduced PSH).…”
Section: Moult Oxidative Status and Sex Differencessupporting
confidence: 62%
See 2 more Smart Citations
“…Hence, moult may result in redox imbalance, but this topic has not been thoroughly addressed. A previous study showed that barn swallows (Hirundo rustica) at initial stages of flight feather moult had higher glutathione S-transferase activity and lipid hydroperoxides than birds that had nearly terminated moult, suggesting that moult, either directly or indirectly via increased energy expenditure due to handicapped flight, may cause oxidative stress (Raja-aho et al, 2012). Our findings strongly suggest that moult resulted in higher protein oxidative damage (reduced PSH).…”
Section: Moult Oxidative Status and Sex Differencessupporting
confidence: 62%
“…In the analyses, we included normalized tGSH (μmol l −1 g −1 Hb) and the GSH:GSSG ratio (higher values reflect low oxidative stress conditions) (e.g. Raja-aho et al, 2012).…”
Section: Determination Of Circulating Gshmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in oxidative stress over the year can be related to excess production of ROS and/or the periodic overwhelming of the antioxidant system by parasites and the activated immune system (Schaefer et al 2008;Sorci and Faivre 2009;Cohen et al 2010). The limited number of studies investigating oxidative physiology over the year have provided mixed evidence perhaps because of variation in methodologies to assess oxidative status, taxonomic differences, varying environmental conditions, or sampling that covered only a limited period of the year Norte et al 2009;van de Crommenacker et al 2011;Raja-aho et al 2012;Rubolini et al 2012;Pap et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Una de las limitaciones al utilizar biomarcadores de estrés oxidativo en estudios ambientales en aves, es la escasez de información acerca de las variaciones estacionales y de los niveles basales en sangre o en tejidos (Raja-aho et al, 2012). En la fauna silvestre, los ciclos anuales están sincronizados con las variaciones temporales del ambiente (fotoperiodo, temperatura, época de lluvia y de sequía y disponibilidad de alimento), afectando la morfología, la fisiología y el comportamiento de los organismos (Wikelski et al, 2008).…”
Section: Introductionunclassified